Geopolitics of climate change-induced conflict and population displacement in West Africa. Issue 3 (4th March 2022) - Lenshie, Nsemba Edward; Ojeh, Vincent Nduka; Oruonye, Emeka Daniel; Ezeibe, Christian; Ajaero, Chukwuedozie; Nzeadibe, Thaddeus Chidi; Celestine, Udeogu U.; Osadebe, Nnabuike
ABSTRACT: Climate change has remained a major problem around which global development policies are framed. The effects of climate change are rising tremendously and are more evident in Africa with low adaptive capacity to the impacts of climate change and where climate change has led to drought and desertification with consequences for safety and security in the region. Although the connection between climate change and conflicts is well studied, there is little research on the geopolitical contribution of climate change to conflicts. Using a dominant qualitative approach based on secondary data and eco-violence theory, this study examines how geopolitics affects climate change-induced conflicts and displacement in West Africa. Drawing largely from Nigeria and Mali, the study argues that, despite the destructive effects of anthropogenic activities created by insufficient competing areas for livelihood and subsistence resources, the implementation of climate resolution among countries and regions of the world has remained obscure. The repercussions of the geopolitics of climate change are the insurgencies and cattle herders' unrest in Africa, especially the West African region.